2021
DOI: 10.9734/jpri/2021/v33i56a33908
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Hemoglobin Levels in Pregnant and Non-pregnant Women in Rafha city, Saudi Arabia

Abstract: Background: Anemia is a global health problem especially affecting pregnant and non-pregnant women. Among many different causes of anemia, iron deficiency anemia is the most common cause. Hemoglobin concentration measurement is among the most commonly performed blood tests, usually as part of a complete blood count. Methods: A cross sectional study was conducted in Rafha Central Hospital and three associated health centers. Pregnant and none pregnant women (400) were included in the study. The data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…It is related to increased maternal and child mortality and morbidity in low-income countries [11] In our study, out of 152 pregnant women 90 of them were anaemic (Hb Less than 11) with the prevalence of 59%, This finding was consistent with a study in Sudan were the prevalence was 53.0% [12] and in Jeddah, Saudi Arabia where it was 55.6% [13] , but higher than the studies conducted in Ethiopia [14], and Uganda [15]. However, it is lower than that found by A-Elbasit et al in Rafha city in Saudi Arabia where they found the prevalence of anaemia among pregnant women more than 70% [16]. Such geographical variations of anaemia across the countries might be attributable to the difference in food hepatis and cultural beliefs about dietary consumption during pregnancy, the occurrence of communicable diseases and the difference in the availability of healthcare facilities.…”
Section: Discussion:-supporting
confidence: 88%
See 1 more Smart Citation
“…It is related to increased maternal and child mortality and morbidity in low-income countries [11] In our study, out of 152 pregnant women 90 of them were anaemic (Hb Less than 11) with the prevalence of 59%, This finding was consistent with a study in Sudan were the prevalence was 53.0% [12] and in Jeddah, Saudi Arabia where it was 55.6% [13] , but higher than the studies conducted in Ethiopia [14], and Uganda [15]. However, it is lower than that found by A-Elbasit et al in Rafha city in Saudi Arabia where they found the prevalence of anaemia among pregnant women more than 70% [16]. Such geographical variations of anaemia across the countries might be attributable to the difference in food hepatis and cultural beliefs about dietary consumption during pregnancy, the occurrence of communicable diseases and the difference in the availability of healthcare facilities.…”
Section: Discussion:-supporting
confidence: 88%
“…Zinc and iron are the most important trace elements in homeostasis. Iron and zinc have important roles in heme structure, iron absorption, iron transport and exhibit competitive inhibition in transport and bioavailability [15][16]. Zinc acts as a catalyst in heme metabolism being part of GFi-1B zinc finger protein structure, which is a major regulator in erythroid cell growth by modulating gene expression specific to erythroid series, performs transcriptional regulation during erythropoiesis [22].…”
Section: Discussion:-mentioning
confidence: 99%